The professional liability factor in modern doctrine (2011)
In the frame work of the different theories concerning professional responsibility, this work pretends to present the general criterions established by national and foreign modern specialists to determine when a professional is responsiblefor his/her procedures. This article wants to demonstrate that is possible to findthose general standards to impute professional responsibility, using a descriptive and analytic method. Thus, this study defines professional in terms of thenational and foreign modern studiers of torts, and presents the various criterions to impute responsibility to the agent that correspond to the definition previously stated, shifting with the obligations that every professional has. Thisarticle shows the need to study the standards to impute professional liabilityused by the Colombian jurisprudence.